Risk priorities for the reasons for the spread of sectarian strife in Iraq A study with mathematical analysis - Huda Khalid; Abdul-aziz Aziz; Ahmed Issa; Ahmed Muhammad; Fadel Abdullah (University of Mosul-college of Basic Education, 2024)
There is no doubt that there are reasons for the occurrence of (sectarian, societal, between individuals, between central and local or regional governments) strife, and there are repercussions and results of these strifes. In this research, the researchers are trying to achieve some modern approaches in the mathematical analysis of these causes and their repercussions. In addition to proposing some solutions to the problems that society has suffered from, from the point of view of Iraqi researchers who lived through the events of sectarian strife in Iraq and at the same time adopted the idea of spreading Neutrosophic Logic through their management of the International Neutrosophic Scientific Association (NSIA) / Iraqi Branch, whose main centre in the United States of America is led by the scientist of Roman origin, he is  Prof. Dr. Florentin Smarandache the founder of neutrosophic logic, as the neutrosophic theory is a generalization of the fuzzy theory and is a powerful mathematical tool for analysis and interpretation. Neutrosophic Logic is also characterized by the spread of its scientific research around the world, as hundreds of researchers around the world have adopted the publication of research solid scientific publications in internationally reputable journals have achieved solutions to the problems addressed by these researchers.